PENGARUH LINGKUNGAN INDUSTRI TERHADAP KINERJA PEMASARAN DI KOTA MAKASSAR - Ratna Dewi; Muhammad Syafii A.Basalamah; Nurhayati Azis (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2023)
This research is the influence of the Industrial Environment on marketing performance in MSMEs. The purpose of this study is 1) To simultaneously examine the industrial environment for MSME/catering marketing in Makassar City, 2). Analyze the industry environment partially on marketing performance in MSMEs/catering. This study used a sample of 35 MSMEs / caterers in Makassar City. Data collection using questionnaires and interviews. Descriptive data analysis methods and multiple regression analysis models The results showed that the Industry variables together have a significant influence on the marketing performance of MSMEs/Catering in Makassar. Competition between competitors has a significant influence on marketing performance. The potential entry of new competitors contributes significantly or cynically affects marketing performance Significant value shows that the variable relationship of supplier bargaining power to the marketing performance of catering MSMEs is positive. The results of the study stated that consumer bargaining power directly affects the performance of MSME/Catering Marketing. Consumer bargaining power with indicators contributes significantly to the marketing performance of MSMEs/catering in Makssar City